2021
DOI: 10.3390/sym14010036
|View full text |Cite
|
Sign up to set email alerts
|

Review on Performance Enhancement of Photovoltaic/Thermal–Thermoelectric Generator Systems with Nanofluid Cooling

Abstract: Photovoltaics (PVs) are an effective technology to harvest the solar energy and satisfy the increasing global electricity demand. The effectiveness and life span of PVs could be enhanced by enabling effective thermal management. The conversion efficiency and surface temperature of PVs have an inverse relationship, and hence the cooling of PVs as an emerging body of work needs to have attention paid to it. The integration of a thermoelectric generator (TEG) to PVs is one of the widely applied thermal management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…Many parameters affect PV panel performance, such as technology, design, irradiance, dust, humidity, ambient temperatures, and other environmental parameters [13,14]. These cells are affected by many environmental influences, such as shadows, temperature, relative humidity, and dust [15][16][17][18]. Theoretically, the operation of PV modules under standard conditions (solar radiation intensity of 1000 W/m 2 , air temperature of 25 • C, and air mass of 1.5) results in the highest electrical efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Many parameters affect PV panel performance, such as technology, design, irradiance, dust, humidity, ambient temperatures, and other environmental parameters [13,14]. These cells are affected by many environmental influences, such as shadows, temperature, relative humidity, and dust [15][16][17][18]. Theoretically, the operation of PV modules under standard conditions (solar radiation intensity of 1000 W/m 2 , air temperature of 25 • C, and air mass of 1.5) results in the highest electrical efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…However, the increase in pressure loss and consequently increase in driving power with high nanofluid concentrations can be a limiting factor for its application in PV/T systems (Said et al, 2018). A review of the contemporary developments in PV/T systems revealed an enhancement in thermal and electrical performance compared to standalone PV systems (Garud et al, 2022). The most common nanofluids found in the published literature consist of Al2O3, CuO, ZnO, and SiO2 particles, which have significantly enhanced both electrical and thermal efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, by fitting the TEG with a heat sink, it can cool the PV module by extracting undesired heat, reducing heat-based degradation of the efficiency and lifespan of the PV module. 15 The configuration also allows the full spectrum of solar energy to be utilized by introducing an additional photothermal conversion layer. The photothermal conversion layer between the PV and TEG enables photons in the long-wavelength region to be effectively absorbed.…”
mentioning
confidence: 99%
“…The TEG can utilize the waste heat from the PV, resulting in extra electrical power generation from the same solar energy. In addition, by fitting the TEG with a heat sink, it can cool the PV module by extracting undesired heat, reducing heat-based degradation of the efficiency and lifespan of the PV module . The configuration also allows the full spectrum of solar energy to be utilized by introducing an additional photothermal conversion layer.…”
mentioning
confidence: 99%